A Moderated Mediation Analysis to Further Examine the Role of Verbal Intelligence in the Association Between Psychopathic Personality and Crime - Etzler, Sonja (International journal of offender therapy and comparative criminology, 2023)
The current study examined the association between psychopathy, criminal behavior, and the role of verbal intelligence. One promising approach is to examine alternative links between psychopathic traits and criminality like moderation and mediation effects by considering the potential relevance of verbal intelligence as a possible moderating variable. We hypothesized that psychopathic traits linearly predict antisocial behavior (ASB) but that a conviction because of ASB is moderated by verbal intelligence. To test a path model of this hypothesis, N = 305 participants (42% women; n = 172 inmates of German correctional facilities) filled in questionnaires to assess psychopathic traits, ASB, criminal behavior, and verbal intelligence. The moderated mediation analysis revealed that high psychopathic traits go along with a higher number of ASB, whereas individuals with higher verbal intelligence were more likely to evade detection, thus being more successful in their antisocial acts. These results sheds further light on the construct of adaptive psychopathy, supporting the notion that also non-incarcerated psychopathic individuals act highly antisocial. Only separate factors like verbal intelligence might mitigate negative consequences. Further implications for the concept of successful psychopathy are discussed.